2013
DOI: 10.3855/jidc.2623
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candida blood stream infections: experience of a tertiary care centre in North India

Abstract: Introduction: Bloodstream infections due to Candida species are becoming a major cause of morbidity and mortality in hospitalized patients. The spectrum of candidemia has changed with the emergence of non-albicans Candida species, especially among critically ill patients. Methodology: In a retrospective study (July 2009 to December 2009) on candidemia, various Candida species isolated from blood cultures were characterized and studied along with the determination of their antifungal susceptibility to amphoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
45
5
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 21 publications
12
45
5
1
Order By: Relevance
“…A previous study done at the same hospital by Akbar and Tahawi [9], found that patients with CVCs (77%) who received broad-spectrum antibacterial therapy (87%) were associated with candidemia. The study of Chander et al [6], has similar results to ours regarding associated risk factors with candidemia.…”
Section: The International Arabic Journal Of Antimicrobial Agentssupporting
confidence: 77%
See 1 more Smart Citation
“…A previous study done at the same hospital by Akbar and Tahawi [9], found that patients with CVCs (77%) who received broad-spectrum antibacterial therapy (87%) were associated with candidemia. The study of Chander et al [6], has similar results to ours regarding associated risk factors with candidemia.…”
Section: The International Arabic Journal Of Antimicrobial Agentssupporting
confidence: 77%
“…The spectrum of candidemia has been changed especially among critically ill patients due to emergence of non-albicans Candida (NAC) species, including C. tropicalis, C. parapsilosis, C. krusei, and C. glabrata. The increasing use of azole agents is suggested to be responsible for this epidemiological shift [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There are more than Candida 20 species, the most common of which is Candida albicans. Candidiasis is the fourth most common cause of health care-associated bloodstream infections in India and the United States (1). This yeast normally lives on the skin and mucous membranes without causing infection.…”
mentioning
confidence: 99%
“…In previous studies Candida parapsilosis was next to Candida, 10,13 whereas in few Indian studies Candida tropicalis was the most common species isolated followed by Candida albicans. 14,15 The distribution of the species is different in various regions and studies. Our data also suggested that non-albicans Candida (61%) was the predominant species when compared to Candida albicans (39%), which establishes the importance of non-albicans Candida in causing blood stream infections.…”
Section: Itraconazolementioning
confidence: 99%